MANAJEMEN SUMBER DAYA INSANI - Ali Hardana (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Abstract This is very important in today’s challenging environment for the company to survive and win the competition in the market. A company is required to have a strategic business plan that is supported by human resource planning, and one of the important functions of the Human Resources (HR). Many companies position the HR function only as personnel administration and in addition, the professional resources (human resources) also did not have enough understanding of how to maximize their effectiveness of their role in the company. The question is what HR roles required in order to provide support, useful, and maximize the potential and value of the company. Case study focuses on industrial companies etrochemical. This study found that all companies doing HR human resources planning and continuous where the HR function in the role they play equally balanced in four roles and accompanied by a balance of incentives. Keywords: Human Resource Planning, Selection, incentives